THE EFFECT OF ADDING BIOETHANOL TO RON 92 GASOLINE ON PERFORMANCE AND EXHAUST EMISSIONS - Sugati, Daru; Salim , Amat Agus; Abdulkadir, Muhammad; Efendi , Nizam (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2025)
Processing bioethanol from plants rich in carbohydrates into alternative energy sources is a challenging problem related to providing renewable energy. This paper discusses an experimental study of a spark ignition (SI) engine using a mixture of conventional RON 92 fuel mixed with bioethanol. The aim is to boost engine performance and exhaust emissions caused by bioethanol blended fuels (E5 and E10). An unmodified spark ignition (SI) engine and bioethanol distillation product from sugarcane molasses mixed with conventional RON 92 fuel were used to evaluate engine performance at engine speeds between 2000 and 8000 rpm. The investigation results showed that the mixture of E5 and E10 provided advantages because the oxygen content was higher, thus improving the combustion process. The torque and engine power produced increased by an average of 1.1% and 1.9%. Under the same combustion process conditions, BSFC fuel consumption also decreased by an average of 1% and 2.3%. The mixture of fuel with bioethanol sugarcane molasses can improve the combustion process because it contains a lot of oxygen (O2). The increase in torque and power produced by the engine is not too significant, but overall, it can reduce the content of exhaust emissions of carbon monoxide (CO), carbon dioxide (CO2), and hydrocarbons (HC).